Enhanced light harvesting and charge separation over wormhole mesoporous TiO2-X nanocrystallites towards efficient hydrogen generation - Negi, Sanjay Singh (Sustainable Energy & Fuels, 2019)
Here meso-TiO2-X materials with combined visible light absorption, high surface area, an anatase-rutile heterojunction, and electrically interconnected nanocrystallites in a wormhole mesoporous framework are achieved. Meso-TiO2-X materials were prepared by solution combustion synthesis (SCS), followed by hydrogenation at higher temperatures. The materials are thoroughly characterised by various physicochemical techniques. A small band gap (2.8 eV), type IV-H-2 mesoporosity with a biphasic heterojunction, and small pore depths (10 nm) in a wormhole mesoporous framework are observed with 35AP. Photocatalytic water splitting for hydrogen production and photocurrent generation were carried out with meso-TiO2-X materials under simulated sunlight. A six-fold increase in activity under AM 1.5G irradiation was observed, which is attributed to the generated mid-gap states which lead to band gap reduction, improved optical absorption in the visible and infrared light region resulting in higher charge carrier density. The presence of a biphasic heterojunction between the (1 0 1) anatase and (1 1 0) rutile facets assists in effective charge separation. A low charge diffusional constraint associated with wormhole mesoporosity helps in facile charge transport to the surface for improved charge utilisation in redox reactions.

Efficient olefin epoxidation with high turnover rates over ordered mesoporous silica nanoparticles with uniform manganese sites - Negi, Sanjay Singh; Khatri, Prateek; Singh, Anand Pal (Microporous and Mesoporous Materials, 2023)
Olefin epoxidation has been studied over a series of mesoporous manganese silicate nanoparticles and tBuOOH. Partial substitution of Si by Mn in silica framework leads to highly dispersed, distorted Mn(III) sites, confirmed by various physicochemical analyses. High conversion and stable styrene oxide, stilbene oxide and epoxy cyclohexane yield have been achieved with MS75 with 1:1.5 ratio of olefin: oxidant. However, at faster reaction rates lower styrene oxide yield is observed at lower Mn-containing catalyst (MS100). High TON, TOF over manganese sites shows accessible monomeric Mn sites. Attributed to high reactant density at redox-active Mn silicate sites due to facile diffusion across shallow pore depth channels of nanoparticulate om-MSx and surface hydrophobic characteristics. The catalysts were found to be stable under recycling and filtration experiments. The excellent stability against leaching of active manganese species indicates stable sites and good textural properties in om-MSx, essential for extended activity.
Keywords: epoxidation; Manganese silicates; Mesoporous silica nanoparticles; Ordered mesoporous silica; pH adjustment